Validation of the colposcopic report for screening intraepithelial lesions and cervical cancer - Katz, Leticia M. C.; Vasconcelos, Ana L. R. de; Oliveira, Sydia R. de A.; Resende, Júlio C. P.; Carvalho, Andre L. (International Journal Of Community Medicine And Public Health, 2024)
For optimal cervical cancer care pathway, effective communication among colposcopist professionals regarding colposcopic findings, diagnosis, and treatment of intraepithelial lesions is crucial; standardization of the colposcopic report may serve as a beneficial strategy for this purpose. Elaborate and validate the colposcopic report for screening intraepithelial lesions and cervical cancer using a committee of specialists. This validation study used the item-level content validity index (I-CVI) to verify the agreement of judges per item, and the scale-level content validity index (S-CVI) to determine the mean of the proportion of items classified as "no disagreement"; items with an I-CVI≥0.80 and S-CVI≥0.90 were considered approved. The binomial test was used to select the items that should be revised based on the p value of the proportion (rejecting the H0 if p≤0.8); statistical significance was set at p<0.05. Results: Seven judges participated in this study. The 11 items of the Colposcopic Report were validated, but items classified as “disagreement” (1, 2, 5, and 9) or “neither agree nor disagree” (3, 10, and 11) were taken to a consensus meeting. Six of the seven judges of the first stage participated in the consensus meeting. Suggestions for modifying item nine were not accepted, and item 11 underwent a slight modification. The colposcopic report was validated and achieved greater reliability, suggesting its inclusion in the cancer information system.